Impact of Afirma gene expression classifier on cytopathology diagnosis and rate of thyroidectomy. Issue 10 (27th June 2016) - Sacks, Wendy L.; Bose, Shikha; Zumsteg, Zachary S.; Wong, Ronnie; Shiao, Stephen L.; Braunstein, Glenn D.; Ho, Allen S.
Abstract : BACKGROUND: The Afirma gene expression classifier (GEC) assesses malignancy risk in patients with indeterminate thyroid nodules. Afirma putatively reduces costs by classifying certain nodules as benign and thereby avoiding unnecessary surgery. Prior studies have evaluated its impact exclusively on GEC‐tested nodules. The objective of the current study was to analyze the effect of Afirma on 1) cytopathology diagnosis, 2) the rate of surgery, and 3) the rate of malignancy on all indeterminate nodules at a high‐volume thyroid center. METHODS: A retrospective cohort analysis of indeterminate (Bethesda III/IV) thyroid nodules from 2012 through 2014 was performed. Cases were evaluated from January 2012 to July 2013 (pre‐Afirma), and from July 2013 to December 2014 (post‐Afirma). RESULTS: Of 4292 fine‐needle aspirations (FNAs) performed, 13.2% were classified as indeterminate. The GEC was used in 45.3% of post‐Afirma cases, with the GEC‐Benign call rate at 37.1%. In comparing pre‐Afirma and post‐Afirma cohorts, a significant increase in Bethesda III (10.7% vs 13.4%; P <.005) and Bethesda IV (1.8% vs 2.9%; P <.01) rates were observed. Conversely, the incidence of Bethesda II was found to be significantly decreased (74.6% vs 68.8%; P <.001). The rate of surgery did not change significantly between pre‐Afirma and post‐Afirma cohorts (37.7% vs 45.1%; P = .11), nor did the malignancy rate (25.3% vs 36.0%; P = .12). CONCLUSIONS: The incidence of indeterminate FNA diagnoses significantly increased after Afirma became routinely available, whereas the incidence of benign diagnoses significantly decreased. These data suggest that Afirma may shift FNA interpretation toward Bethesda III/IV, in which molecular testing is used. Moreover, the institutional rates of surgery and malignancy did not appear to change, raising uncertainty regarding the benefits of molecular assay risk stratification. Afirma may produce unintended collateral effects, increasing the number of indeterminate FNA diagnoses while not affecting the institutional thyroidectomy rate or malignancy yield. Cancer Cytopathol 2016;124:722–8 . © 2016 American Cancer Society. Abstract : The Afirma molecular assay may potentially affect thyroid fine‐needle aspiration diagnosis rates. Furthermore, the rate of thyroidectomy may not change after adoption of Afirma.